Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1007/s10457-010-9327-6
|View full text |Cite
|
Sign up to set email alerts
|

Detection of nitrogen transfer from N2-fixing shade trees to cacao saplings in 15N labelled soil: ecological and experimental considerations

Abstract: Theobroma cacao seedlings were grown alone (TCA) or associated with saplings of N 2 -fixing shade trees Gliricidia sepium and Inga edulis in 200 l of 15 N labelled soil within a physical root barrier for studying direct nitrogen transfer between the trees and cacao. Root:shoot partitioning ratio for sapling total N was lower than biomass root:shoot ratio in all species. Sapling total 15 N was partitioned between root and shoot in about the same ratio as total N in cacao and inga but in gliricidia much higher p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 57 publications
3
27
0
Order By: Relevance
“…This lower signal can indicate the occurrence of transference of some of the N fixed by cowpea to the associated trees, as reported by Kurppa et al (2010).…”
Section: Resultssupporting
confidence: 61%
See 2 more Smart Citations
“…This lower signal can indicate the occurrence of transference of some of the N fixed by cowpea to the associated trees, as reported by Kurppa et al (2010).…”
Section: Resultssupporting
confidence: 61%
“…The 15 N abundance of the tree species of the agroforestry system intercropped with maize + cowpea indicated no apparent fixation in gliricidia, as previously mentioned. The reason for this absence of fixation is not known and it is intriguing because gliricidia is considered a species with high N 2 -fixing capacity (Paulino et al, 2009;Kurppa et al, 2010), and the trees fixed abundantly when intercropped with buffel grass and prickly-pear cactus.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in a legume-cacao association, Kurppa et al ( 2010 ) found limited net N transfer from associated legume tree species to cacao in spite of active N 2 fi xation. No response to N application has generally been found in fertilizer trials, particularly in Côte d'Ivoire (Lotodé and Jadin 1981 ), Ghana , or Sri-Lanka (Heenkende and Gunarantne 2000 ).…”
Section: Role Of Nutrients In Fertilizer and Recommendation For Theirmentioning
confidence: 99%
“…However, as nitrogen concentrations and δ 15 N values of mature leaves of TGli trees were not significantly different from TGua trees and TSol trees, our findings suggest that even 4 years after plantation establishment atmospheric nitrogen fixed by G. sepium is not bioavailable in quantities that enhance nitrogen content of T. rosea leaves. The lack of detectable nitrogen transfer may be related to missing direct belowground interactions through root exudates or interconnected mycelial networks (Sierra and Nygren 2006) or to an absence of indirect interactions actually driven by the decomposition of nitrogen-enriched G. sepium biomass (Kurppa et al 2010).…”
mentioning
confidence: 99%